Parental Participation in Early Childhood - Hannami Putri, Fidella; Putri Ramadhani, Aliyyah; Ananda, Rizka; Dwi Andika, Windi; Fathiah, Najlatul (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to explore parental participation in early childhood education using a qualitative approach and semi-structured interview method. The informants consisted of five parents who have children aged 3–6 years enrolled in early childhood education (PAUD) institutions. Informants were selected purposively based on their involvement in their children's education. Data were collected through in-depth interviews and analyzed using data reduction, data presentation, and conclusion drawing techniques. Bronfenbrenner’s Ecological Systems Theory was used as a framework to understand how the microsystem, such as the family environment, plays a vital role in a child’s development. The results show that parental participation is influenced by internal factors, such as educational awareness, and external factors, such as social and economic support. The study recommends that early childhood institutions build stronger communication and partnerships with parents to enhance their engagement in their children's education.